Clinical features among adult‐onset type 1 diabetes, distribution of subtypes, and differences in probable and definite slowly progressive insulin‐dependent diabetes mellitus: A single hospital‐based study over a 13‐year period - Hiroko Takaike; Junnosuke Miura; Satoshi Takagi; Shota Mochizuki; Tetsuya Babazono (Journal of Diabetes Investigation)
ABSTRACT Aims In Japan, type 1 diabetes (T1D) is classified into three subtypes based on its onset patterns; however, the proportion of each subtype remains unexplored. To elucidate the heterogeneity in adult‐onset type 1 diabetes, we compared the frequencies of subtypes and clinical features by age at onset. Materials and Methods This cross‐sectional, observational, single‐institution study included 482 individuals (161 male) with T1D. The clinical and laboratory data, including glutamic acid decarboxylase autoantibodies, were extracted from the medical records. Results The number of adults who developed T1D decreased with age. Among all patients, 62% (n = 299) had acute‐onset T1D, 27% (n = 131) had slowly progressive T1D (SPIDDM), and 11% (n = 52) had fulminant T1D. The proportion of patients with fulminant T1D was approximately equivalent in all age groups; however, the percentage of patients with acute‐onset T1D decreased from 78% in the 20–29 age group to 27% in the 70–79 age group. The proportion of patients with SPIDDM significantly increased with age, ranging from 16% in the 20–29 age group to 60% in the 70–79 age group. Among patients with SPIDDM, the prevalence of definite SPIDDM was 89%, and this prevalence did not differ based on the age at onset. Body mass index and C‐peptide levels among patients with probable SPIDDM were significantly higher than those among patients with definite SPIDDM. Conclusions The proportion of adult‐onset T1D subtypes differed according to the age at onset. In adult‐onset T1D, some etiological differences may be based on age at onset.